Implementation of Lean and Capacity Planning to Improve Food Truck Operational Efficiency as a Business Expansion Preparation Strategy - Firdausi, Amaltea Fatimah; Aziz, Anton Mulyono (International Journal of Digital Marketing Science, 2026)
This study examines how Lean principles and capacity planning can enhance operational efficiency in small food businesses, focusing on Yokoso Neng Ikah, a food truck operating in Yaizu City, Japan. The business has faced persistent challenges, including long customer wait times, raw material waste, and uneven staff workloads during peak hours. While Lean and capacity planning are well-established in manufacturing and large service industries, there is limited research on their application in mobile food enterprises. This research aims to fill that gap by exploring how these strategies can streamline workflows, reduce inefficiencies, and improve labor management in a micro-enterprise context. Using a quantitative descriptive approach, data were collected through surveys with 40 respondents comprising the owner, managers, and staff. The data were analyzed with SPSS 31.0 using descriptive statistics to assess current operational practices and the effectiveness of Lean and capacity planning implementations. Results show that Lean tools such as visual aids and standardized routines have been moderately adopted and contributed to simplifying tasks, while flexible scheduling helped manage busy periods more effectively. However, responsiveness to sudden demand spikes remains limited, indicating room for improvement. Overall, this study demonstrates that Lean and capacity planning, although traditionally applied in larger-scale operations, can be successfully adapted to small-scale food service businesses, providing both practical recommendations for improving operational efficiency and contributing valuable insights to the field of micro-enterprise management. Keywords: Capacity; food trucks; Lean; MSMEs; operational efficiency; SPSS